PROTOTYPE DESIGN OF A REGENERATIVE DAMPER-BASED ENERGY HARVESTER FOR PLAYGROUND SEESAW - Dhiya Ul Haq, Muhammad
Increasing demand for electricity, coupled with greater understanding of the environmental impact of conventional power generation, have led to growing research interest on alternative energy sources. Energy harvesters based on playground equipment, such as the seesaw, has recently been proposed as an alternative method to generate electrical power. This final year project presents the design, fabrication, and testing of a prototype playground seesaw-based energy harvester. The energy harvester consists of a regenerative damper and power conditioning circuit. A regenerative damper utilizing freewheel mechanism converts linear oscillating motion from a playground seesaw to DC electricity. Power conditioning circuit regulates the voltage produced by the regenerative damper as appropriate for the given electrical load. Lab tests have been carried out to experimentally characterize the proposed design. The energy harvesting (stroke velocity-to-voltage) coefficient for the proposed seesaw-based energy harvester is obtained as 73,18 V/(ms^(-1)). The regenerative damper is capable of producing up to 110,00 mW of power with efficiency up to 9,34%, while the power conditioning circuit is capable of stabilizing the output voltage of the regenerative damper and produce up to 34,11 mW of power from the regenerative damper with efficiency up to 21,05%. Keywords: seesaw, alternative energy, energy harvesting, regenerative damper, power conditioning